Strategic Planning and Cooperative Strategies For Sustainability: A Framework for Effective Decision Making and Competitiveness (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Organizations  need to  continually  change in  order  to survive  and to  grow; this  is  especially true  in the competitive marketsand in market based  economies. However,over emphasis on change can be a deterrent to organizational growth. It istherefore essential to correctly identify areas and reasons for change.Critical  decisions  of identifying  the  areas, and  order  of change  that would  lead to  a  path of  sustainability  and growth  for  an organization  require  a decisive  assessment  process. At each phase of a decision making process, there are numerousnondeterministic choices and the certainty of success may be influenced by manyexternal factors. External factors affecting an organization include marketforces such as, competition, user demand, and suppliers, in addition topolitical, legal, and environmental factors. These in turn influence internalefficiencies of its components: divisions, product lines, and Strategic Business Units- grouped togetheras Value Components (VC). In this paper, we present methodologies fororganizations to recognize areas and rationale for change, and to identifyoptions available for change. Our model for these methodologies is generic asit explores effective ways to leverage cooperative strategies forcompetitiveness and applies to all industries. We elaborate on issues andknowledgebase required for critical VC of a corporation, and on understandingthe limits of efficiencies that can be achieved. A conceptual framework thatemerges from the model provides systematic guidelines for critical decisionmaking.